2021
DOI: 10.1002/1348-9585.12221
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health nurses’ personal attitudes toward smoking: A cross-sectional study

Abstract: Objectives This study aims to investigate if experience in smoking intervention training influences attitudes toward smoking, discuss the role of health management programs of small‐ and medium‐sized enterprises, and analyze the current attitude of occupational health nurses regarding the hazards of smoking and responsibility to smokers to effectively facilitate smoking cessation support programs. Methods We conducted an anonymous self‐administered cross‐sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The workplace appears to be a useful setting to help people quit smoking if it has an adequate professional antismoking program 2 . Previous studies have suggested that OHNs need to be provided with opportunities to increase their smoking cessation intervention techniques and their roles as smoking advisors to promote occupational health in small-and mediumsized enterprises (SMEs) in Korea 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The workplace appears to be a useful setting to help people quit smoking if it has an adequate professional antismoking program 2 . Previous studies have suggested that OHNs need to be provided with opportunities to increase their smoking cessation intervention techniques and their roles as smoking advisors to promote occupational health in small-and mediumsized enterprises (SMEs) in Korea 3 .…”
Section: Introductionmentioning
confidence: 99%